Evaluation of laboratory turnaround times of chemical pathology test requests at Centre For Pathology Diagnostic And Research Laboratories (CPDRL) Sungai Buloh, Faculty of Medicine UiTM / Nor Fazirah Rozali - Rozali, Nor Fazirah (2015)
Laboratory turnaround time (LTAT) is an important indicator of laboratory effectiveness and quality of care. The study aim to evaluate the laboratory TAT in Chemical Pathology at Centre for Pathology Diagnostic and Research Laboratories (CPDRL) Sungai Buloh based on selected test requests and the literatures regarding laboratory TAT, it is focusing on the different definitions, measures, expectations, published data, associations with clinical outcomes and approaches to improve TAT. The study may encourage implementation of TAT monitoring for continuous quality improvement. TAT of renal profile and troponin T (urgent sample), fasting plasma glucose and liver function test (in-patient sample), lipid profile and thyroid function test (routine out-patient sample) was measured starting from initial steps such as specimen reception into laboratory, specimen register using computer system, performing and processing the specimen’s test requests until finalized results were obtained and validated by science officer. The average TAT for the chemical pathology samples were 4 hours for routine inpatient samples while the TAT for the outpatient samples were 5 working days. The TAT for urgent samples was 1 hour. Percentage of achieved TAT were calculated. Percentage for urgent samples were 93%, in-patient samples were 96% and out-patient samples were 100%. These analyze data were found to contribute approximately 96% of the total TAT. In contrast of the study, there are less probability of getting higher delayed of TAT. At the same time, the performance of chemical pathology laboratory services and the quality of handling and processing on patient’s sample and physician reports become reliable because processing-to-releasing patient’s results can be done within the standard duration TAT for each tests requested. The TAT demonstrates the laboratory requirements for improvement of laboratory quality and services. Lower percentage of total TAT due to the certain factors can delayed the period between specimen’s arrival and accessioning of results. Laboratories must ensure that TAT reports were in-controlled continuously for future so that they can perform optimally according to clinician expectations